Identification and characterization of the herpes simplex virus type 1 protein encoded by the UL37 open reading frame. - Shelton, L S (1990)
The UL37 open reading frame of the herpes simplex virus type 1 (HSV-1) DNA genome is located between map units 0.527 and 0.552. We have identified and characterized the UL37 protein product in HSV-1-infected cells. The presence of the UL37 protein was detected by using a polyclonal rabbit antiserum directed against an in vitro-translated product derived from an in vitro-transcribed UL37 mRNA. The UL37 open reading frame encodes for a protein with an apparent molecular mass of 120 kDa in HSV-1-infected cells; the protein's mass was assigned on the basis of its migration in sodium dodecyl sulfate-polyacrylamide gels. The UL37 protein is not present at detectable levels in purified HSV-1 virions, suggesting that it is not a structural protein. Analysis of time course experiments and experiments using DNA synthesis inhibitors demonstrated that the UL37 protein is expressed prior to the onset of viral DNA synthesis, reaching maximum levels late in infection, classifying it as a gamma 1 gene. Elution of HSV-1-infected cell proteins from single-stranded DNA agarose columns by using a linear KCl gradient demonstrated that the UL37 protein elutes from this matrix at a salt concentration similar to that observed for ICP8, the major HSV-1 DNA-binding protein. In addition, computer-assisted analysis revealed a potential ATP-binding domain in the predicted UL37 amino acid sequence. On the basis of the kinetics of appearance and DNA-binding properties, we hypothesize that UL37 represents a newly recognized HSV-1 DNA-binding protein that may be involved in late events in viral replication.